Effect of Ribavirin Alone or Combined with Silymarin on Carbon Tetrachloride Induced Hepatic Damage in Rats - Omar M.E. Abdel Salam; Amany A. Sleem; Enayat A. Omara; Nabila S. Hassan (AboutScience Srl, 2007)
The effect of the antiviral agent ribavirin given alone or in combination with silymarin on the development of liver injury induced in rats with carbon tetrachloride (CCl4; 2.8 ml/kg followed by 1.4 ml/kg after one week) was studied. Ribavirin at three dose levels (30, 60 or 90 mg/kg), silymarin (25 mg/kg) or combination of ribavirin (60 mg/kg) and silymarin (25 mg/kg) was administered once daily orally for 14 days, starting at time of administration of CCl4. The administration of ribavirin decreased the elevations in serum alanine aminotransferase (ALT) by 78.5, 82.1, 75.1%, aspartate aminotransferase (AST) 47.5, 37.4, 38.8%, and alkaline phosphatase (ALP) by 23.4, 16, 21.6%, respectively and also prevented the development of hepatic necrosis caused by CCl4. In comparison, the elevated serum ALT, AST and ALP levels decreased to 43.3%, 46%, and 37.5% of controls, respectively by silymarin. When silymarin was combined with ribavirin, the serum activities of AST and ALP were further decreased, indicating a benefi cial additive effect. Morphometric analysis indicated signifi cant reduction in the area of necrosis and fi brosis on ribavirin treatment and this was further reduced after the addition of silymarin. Metabolic pertuberations caused by CCl4 as refl ected in a decrease in intracellular protein content in hepatocytes were improved by ribavirin monotherapy and to higher extent by combined silymarin and ribavirin therapy. Proliferating cell nuclear antigen was reduced in nuclei of hepatocytes by ribavirin montherapy or the combination of ribavirin and silymarin compared with CCl4-control group. The study demonstrates that ribavirin treatment in the model of CCl4- induced liver injury results in less liver damage. Results also indicate that the combined application of ribavirin and silymarin is likely to be a useful additive in reducing liver injury.